1970
DOI: 10.4314/ahs.v19i4.27
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and maternal socio-demographic factors associated with stillbirth in health facilities in Anambra, South-East Nigeria

Abstract: Background: Stillbirth is a major adverse perinatal outcome especially in low and middle income countries across the globe. Certain factors relating to mothers from such countries may be associated with this adverse condition.Objectives: To determine the prevalence of stillbirth and also explore the maternal socio-demographic factors associated with stillbirth among mothers in rural communities in Anambra Central Senatorial District of Anambra State Nigeria who gave birth between January 2012 and December 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
7
1
Order By: Relevance
“…A similar study corroborated our findings. 17 Other studies however, contradicts the findings of our study reporting that still birth was higher among less educated women. 18,23,25,26 Other studies have also shown that stillbirth was higher in women with no formal education with the rate of stillbirth decreasing with increasing educational status.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…A similar study corroborated our findings. 17 Other studies however, contradicts the findings of our study reporting that still birth was higher among less educated women. 18,23,25,26 Other studies have also shown that stillbirth was higher in women with no formal education with the rate of stillbirth decreasing with increasing educational status.…”
Section: Discussioncontrasting
confidence: 88%
“…23 Other studies contradict this finding and reported that unemployed women had higher prevalence of still birth. 17,24 Our study found out that the rate of still birth was more among women with secondary education compared to women with primary education. This was surprising as higher educational level was supposed to be protective of still birth as better educated women are better equipped to take care of themselves during pregnancy.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations